Compressive strength of one-part alkali activated fly ash using red mud as alkali supplier. (30th October 2016) - Choo, H.; Lim, S.; Lee, W.; Lee, C.
Highlights: One-part mix alkali activated materials were developed using only waste materials. Fly ash with high unburned carbon content was used as an aluminosilicate precursor. Red mud was used as a NaOH supplier in the geopolymerization of fly ash. UCS of inorganic polymers activated with red mud and NaOH were measured. The developed materials can be used as controlled low strength materials. Abstract: Because both fly ash with high unburned carbon particles and red mud are waste materials with very low reuse rates, the reuse of these two waste materials is environmentally and economically beneficial. This experimental investigation aims at developing one-part mix alkali activated materials using only waste materials. Therefore, this study uses fly ash with high unburned carbon particles (or high loss on ignition) as an aluminosilicate precursor and uses red mud as a NaOH supplier in the geopolymerization of fly ash. The results of this study demonstrate that the unconfined compressive strength of the developed one-part fly ash inorganic polymers activated with red mud increases with an increase in red mud content because of the active dissolution of silica and aluminum with an increase in red mud and a consequent promotion of the polycondensation process. The comparison between the inorganic polymers activated with red mud and NaOH pellets reveals that the relation between compressive strength and the Na/Si ratio of the tested inorganic polymers activated with red mud is almost the same as that of the tested inorganic polymers activated with NaOH, reflecting that all solid NaOH (or Na2 O) in red mud can be dissolved to form highly alkaline solutions. Therefore, one-part alkali activated fly ash can be synthesized using red mud as a solid alkali activator.